BNT1 immune receptor alternative spliced variants: Potential role(s) in plastid responses - Peppino Margutti, Micaela Yesica (2020)
Plants depend on a non-adaptive immune system triggered by receptors after the detection of pathogens. Nucleotide-binding leucine-rich repeat receptors (NLRs) are key sensors that recognize specific effectors (or effector-induced alterations) used by pathogens to promote their virulence. Several studies indicate that NLRs can exert their function at the nucleus, plasma membrane, cytoplasm, or the endomembrane system. However, NLRs acting from plastids have never been described. Interestingly, results from our group showed that the BNT1 immune receptor from Arabidopsis is targeted to plastids envelope. Thus, activation of this NLR could modulate organelle-specific responses required for a normal defense, like the production of defense-related metabolites and/or induction of plastid-nucleus retrograde communication. Supporting this idea, our preliminary results showed that overexpression of BNT1 mutated versions induces plastids to cluster around nuclei. Here, we analyzed BNT1 expression profiles in different developmental stages, stress conditions, and/or chemical treatments. Analysis of RNA-seq databases showed that BNT1 transcript levels change in seedlings grown under light or dark conditions. Moreover, it also revealed three different BNT1 isoforms generated by alternative splicing (AS) in the gene 5’ UTR. Our RT-PCR studies validated the presence of these splice variants and indicated that their relative abundance is affected by known splicing factors. We also observed expression differences under heat-stress and in response to exogenous treatments with immunity inducers, hormones, and methyl viologen. Curiously, only one of the BNT1 isoforms exhibits a complete plastid targeting signal. This strongly suggests that AS at the 5’ UTR can control the BNT1 subcellular localization and site of action. The elucidation of BNT1 biological role and its regulation by AS could represent a new paradigm to understand the function of NLRs at different cellular compartments.